Public Confidence in Religious Leaders: A Perspective from Secularization Theory - Kleiman, Michael B. (Review of religious research, 1996)
Scholars studying religion as a social institution have struggled to explain two contradictory trends. Secularization theory posits America as increasingly less religious, yet religious participation and other indicators of spirituality remain high. Our study provides information critical to this debate by employing national data collected over a 22 year period to analyze the public's lack of faith in religious leaders as distinguished from individual levels of religiosity. Findings indicate that public confidence in religious leaders has fallen sharply -- both for the population as a whole and for every demographic subgroup -- whereas personal commitment to religion itself has grown. These results are important because they provide an empirical test of newer theories which describe secularization as a loss of the influence of religious authority rather than a decline in individual piety. We discuss the implications of our findings, not only for secularization theory but also for organized religion itself.